Hyper-dominant Left Anterior Descending Artery in the coronary circulation as a rare coronary anomaly - Pandey, Brijesh; Karki, Prahlad; Pandey, Naveen Kumar; Ghimire, Jeet Prasad; Karki, Biplave; Gyawali, Achyut; Pandey, Shikha (Nepalese Heart Journal, 2023)
Hyper-dominant left anterior descending artery is rarely seen in the coronary distribution. Its involvement in ACS can often be detrimental as it supplies most of the anterior and inferior part of the right and left ventricles in compared to other variants of LAD artery. It is required to be recognized earlier and management strategies should be ascertained. Our report here describes such a case of anomalous coronary artery which is less commonly encountered during Coronary Angiography. This was case of a 60 year old hypertensive male who presented with atypical chest pain had normal ECG, echocardiography and cardiac biomarkers but TMT was positive, subsequent Coronary angiographic evaluation came up with LAD artery which was going beyond apex in the posterior interventricular groove up to crux forming PDA with 20 to 30% stenosis in proximal to distal part. Such a large LAD running into the interventricular groove forming PDA is known as “Hyper-dominant” LAD artery. The Right Coronary artery was non-dominant. Fortunately, there was no signifcant coronary artery disease to explain the cause of his chest pain, but the artery had unusual distribution provided that it has sole territorial supply to larger part of the myocardium which can worsen the clinical status if coronary artery disease progresses. He was kept under medical management and was doing good. The “Take away” lesson is that there are very few subjects with Hyper-dominant LAD artery till date and most other cases with this anatomy had presented with myocardial infarction and thus such anatomical variant of LAD artery ought to be matter of concern and further research in the feld of cardiology.